2021
DOI: 10.1177/24730114211060063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Complications With Open vs Minimally Invasive Achilles Tendon Repair

Abstract: Background: There is no current consensus on whether to use an open or minimally invasive (MIS) approach for Achilles tendon repair after acute rupture. We hypothesized that patients in both open and MIS groups would have improved patient-reported outcome scores using the PROMIS system postoperatively, but that there would be minimal differences in these scores and complication rates between operative techniques. Methods: A total of 185 patients who underwent surgery for an acute, unilateral Achilles tendon ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
(106 reference statements)
0
6
0
5
Order By: Relevance
“…Furthermore, through improvements between preoperative and postoperative PROMIS scores, this study demonstrated responsiveness in PROMIS after both open and MIS repair, suggesting that both groups have similar long-term outcomes. 6 Another study demonstrated responsiveness between preoperative and postoperative PROMIS PF CAT and PI CAT scores among 62 patients with ruptured Achilles tendon who underwent surgery, suggesting the validity of PROMIS to evaluate Achilles tendon rupture treatment options. However, improvements in PROMIS scores did not automatically translate to clinically meaningful changes, as only 47% of patients in the Achilles PROMIS PF CAT domain achieved MCID of 3.0 to 4.5.…”
Section: Foot and Ankle Tendon Injuriesmentioning
confidence: 98%
“…Furthermore, through improvements between preoperative and postoperative PROMIS scores, this study demonstrated responsiveness in PROMIS after both open and MIS repair, suggesting that both groups have similar long-term outcomes. 6 Another study demonstrated responsiveness between preoperative and postoperative PROMIS PF CAT and PI CAT scores among 62 patients with ruptured Achilles tendon who underwent surgery, suggesting the validity of PROMIS to evaluate Achilles tendon rupture treatment options. However, improvements in PROMIS scores did not automatically translate to clinically meaningful changes, as only 47% of patients in the Achilles PROMIS PF CAT domain achieved MCID of 3.0 to 4.5.…”
Section: Foot and Ankle Tendon Injuriesmentioning
confidence: 98%
“…Overall, open Achilles tendon repair provides adequate restoration of tendon tension and plantarflexion strength, low rerupture and sural nerve injury rates, return to activity and improvement in patient-reported outcomes (PROs) 30–32 . Outcomes after open Achilles tendon repair are comparable to other treatment modalities, such as minimally invasive techniques or nonoperative management.…”
mentioning
confidence: 98%
“…25 Overall, open Achilles tendon repair provides adequate restoration of tendon tension and plantarflexion strength, low rerupture and sural nerve injury rates, return to activity and improvement in patient-reported outcomes (PROs). [30][31][32] Outcomes after open Achilles tendon repair are comparable to other treatment modalities, such as minimally invasive techniques or nonoperative management. Although much of the literature has shown no differences in complication rates among surgical techniques and nonoperative management, the main differences to consider are possible increased risk of wound complications with open repair, decreased rerupture risk with surgery compared with nonoperative treatment, and decreased risk of sural nerve injury with open and nonoperative treatment compared with percutaneous minimally invasive approaches.…”
mentioning
confidence: 99%
See 2 more Smart Citations